(untitled) (Journal of Global Arts Studies, 2025)
Background: As the root of Chinese civilization, Qilu Culture gains policy-driven communication progress but suffers from homogenization and cross-cultural value identity dilemmas. Objective: This study aims to analyze Qilu Culture’s communication status and obstacles, build a targeted strategy system to leap to value identity. Methods: Supported by relevant theories, it adopts empirical methods to construct models and systematically analyze factors influencing value identity. Results: A four-dimensional strategy and three-stage identity path are constructed, with remarkable results achieved in pilot regions after practice. Conclusion: The strategy breaks identity barriers, supporting Qilu Culture’s innovative development and Chinese culture’s global communication.